2014
DOI: 10.1186/1471-2393-14-290
|View full text |Cite
|
Sign up to set email alerts
|

Assessing predictors of delayed antenatal care visits in Rwanda: a secondary analysis of Rwanda demographic and health survey 2010

Abstract: BackgroundEarly initiation of antenatal care (ANC) can reduce common maternal complications and maternal and perinatal mortality. Though Rwanda demonstrated a remarkable decline in maternal mortality and 98% of Rwandan women receive antenatal care from a skilled provider, only 38% of women have an ANC visit in their first three months of pregnancy. This study assessed factors associated with delayed ANC in Rwanda.MethodsThis is a cross-sectional study using data collected during the 2010 Rwanda DHS from 6,325 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
83
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(121 citation statements)
references
References 22 publications
25
83
6
Order By: Relevance
“…Recently published data have shown that increased use of iron and reduced anemia are directly proportional to good quality antenatal care, with 6 or more visits starting early in the pregnancy [12,20]. However, in the current study, no relationship was seen between anemia rates and the number of antenatal care visits or the time of presentation (p>0.05).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Recently published data have shown that increased use of iron and reduced anemia are directly proportional to good quality antenatal care, with 6 or more visits starting early in the pregnancy [12,20]. However, in the current study, no relationship was seen between anemia rates and the number of antenatal care visits or the time of presentation (p>0.05).…”
Section: Discussioncontrasting
confidence: 54%
“…Participation in antenatal care was lower in those with a low level of education, even though healthcare was provided and accessible. Higher participation in antenatal care has been observed in groups with a relatively better socio-cultural and educational level in under-developed populations [8,12,13]. The association of level of education with the number of visits and early presentation can be explained by various factors, including greater overall health awareness, earlier realization of pregnancy, and use of related resources [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Independent studies conducted in USA and some African countries reported that there is significant relationship between late ANC and being planned pregnancy. [16][17][18]22,28 Parity is also reported as a significant predictor of late initiation of ANC in studies done in UK, 20 Zambia, 17 Rwanda 22 and Ethiopia. 28 Besides, similar studies conducted in USA and Malawi revealed that maternal education has significant effect on receiving late ANC.…”
Section: Discussionmentioning
confidence: 99%
“…14,19 However, studies conducted in developed countries revealed lower proportions (4.4% to 27.3% % in USA, about 15% in UK and 41% in Australia) whereas some African studies reported comparable or higher values (53% in Ethiopia, 61.1% in Rwanda, 70.3% in Zambia, 81% in Nigeria, more than 70% in Tanzania and Malawi). 5,[16][17][18][20][21][22][23][24][25] Utilization of different cut-off points in defining late initiation of ANC could explain these discrepancies (first trimester or 12 completed weeks was used in USA and UK studies, 16 weeks in Ethiopian, Zambian, Tanzanian and Malawi studies, and second/third trimester in some studies). 5,[16][17][18][19][20]22,24,25 The proportions of pregnant women who initiate ANC before 4 months of gestation among neighboring and ASEAN countries were 40.4% in Bangladesh, 32.2% in Cambodia, 56.9% in India, 78.6% in Indonesia, 37.5% in Nepal, 46.9% in Pakistan, 56.1% in the Philippines and 65% in Vietnam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation